C. S. Lewis: Writing and Publishing Literary Criticism with Oxford University Press and Cambridge University Press - Rayner, Samantha; Searle, Alison (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2019)
This essay uses unpublished archival material to explore what this reveals about the commissioning, gestation, editing, and publishing of several key works of literary criticism by C. S. Lewis: The Allegory of Love: A Study in Medieval Tradition (1936), The Oxford History of English Literature in the Sixteenth Century Excluding Drama (1954), Studies in Words (1960), and The Discarded Image (1964). Our analysis looks at a range of connecting areas, including the complex labour structures and systems of patronage which operated during the period under consideration, as well as the peer review processes, assessments of potential reading markets, the practicalities of authorial revision and typesetting, and the intersections between pedagogical practice and publishing which all these demonstrate. The materials in the archives we drew upon to conduct this research were author marketing questionnaires; book cover designs; letters between Lewis, his press editors, bibliographers, and press reviewers; and cuttings from post-publication reviews. This case study makes an important contribution to our understanding of the role played by mid-twentieth century academic publishers to the production of knowledge in the English-speaking world.